Macro-site selection and obstacle factor extraction of biomass cogeneration based on comprehensive weight method of Game theory - Jing Gao; Zhenfeng Wang; Zhanwu Wang; Chao Wang; Runkai Zhang; Guangyin Xu; Xin Wu (Energy Reports, 2022)
Biomass energy can reduce the consumption of fossil fuels and reduce environmental pollution. The project site selection affects the production efficiency and economic benefits. Firstly, this study proposes a macro-site selection decision framework for biomass cogeneration considering carbon emission reduction. Secondly, this paper innovatively uses Nash equilibrium as the coordination goal, and introduces Game Theory to determine the optimal combination weight of Best-Worst Method (BWM) and Criteria Importance Though Intercriteria Correlation (CRITIC). Further thinking is needed to improve the comprehensive closeness measurement method, establish a Technique for Order Preference by Similarity to an Ideal Solution and Grey Relational Analysis (TOPSIS-GRA) site selection model that reflects distance and curve shape, and sort the plans. And then explore the barriers to improving the site selection environment. Finally take five cities in China as an example. The feasibility and the stability of the site selection decision-making framework in practical applications are verified by comparative analysis and weight sensitivity analysis. The results show that carbon emission is the primary barrier factor in the criterion layer. In the sub-criterion layer, transportation costs, carbon emission pressure, carbon benefits, industrial policies, and heating rate are the common obstacle factors in each region. To promote the long-term healthy development of the project, this study provides a theoretical reference for the new construction and expansion of biomass cogeneration projects, and has guiding significance for improving the location suitability of the project.